KIR3DL1-Negative CD8 T Cells and KIR3DL1-Negative Natural Killer Cells Contribute to the Advantageous Control of Early Human Immunodeficiency Virus Type 1 Infection in HLA-B Bw4 Homozygous Individuals - Zhang, Xin; Lu, Xiaofan; Moog, Christiane; Yuan, Lin; Liu, Zhiying; Li, Zhen; Xia, Wei; Zhou, Yuefang; Wu, Hao; Zhang, Tong; Su, Bin (Frontiers in Immunology, 2018)
Bw4 homozygosity in human leukocyte antigen class B alleles has been associated with a delayed acquired immunodeficiency syndrome (AIDS) development and better control of human immunodeficiency virus type 1 (HIV-1) viral load than Bw6 homozygosity. Efficient CD8 T cell and NK cell functions have been described to restrain HIV-1 replication. However, the role of KIR3DL1 expression on these cells was not assessed in Bw4-homozygous participants infected with HIV-1 CRF01_A/E subtype, currently the most prevalent subtype in China. Here, we found that the frequency of KIR3DL1-expressing CD8 T cells of individuals homozygous for Bw6 (1.53% [0–4.56%]) was associated with a higher viral load set point (Spearman rs=0.59, P=0.019), but this frequency of KIR3DL1+CD8+ T cells (1.37% [0.04–6.14%]) was inversely correlated with CD4 T-cell count in individuals homozygous for Bw4 (rs=-0.59, P=0.011). Moreover, CD69 and Ki67 were more frequently expressed in KIR3DL1-CD8+ T cells in individuals homozygous for Bw4 than Bw6 (P=0.046 for CD69; P =0.044 for Ki67), although these molecules were less frequently expressed in KIR3DL1+CD8+ T cells than in KIR3DL1-CD8+ T cells in both groups (all P<0.05). KIR3DL1-CD8+ T cells have stronger p24-specific CD8+ T-cell responses secreting IFN-γ and CD107a than KIR3DL1+CD8+ T cells in both groups (all P<0.05). Thus, KIR3DL1 expression on CD8 T cells were associated with the loss of multiple functions. Interestingly, CD69+NK cells lacking KIR3DL1 expression were inversely correlated with HIV-1 viral load set point in Bw4-homozygous individuals (rs=-0.52, P=0.035). Therefore, KIR3DL1-CD8+ T cells with strong early activation and proliferation may, together with KIR3DL1-CD69+NK cells, play a protective role during acute/early HIV infection in individuals homozygous for Bw4. These findings highlight the superior functions of KIR3DL1-CD8+ T cells and KIR3DL1-CD69+NK cells being a potential factor contributing to delayed disease progression in the early stages of HIV-1 infection.